Advances in Research on the Interaction of Food-derived Polysaccharide and Polyphenol - Jun HE; Mengdie WANG; Xiaoqiang CHEN; Miaomiao YING (Shipin gongye ke-ji)
Polysaccharides and polyphenols are important active substances in many foods and their raw materials. The interaction of polysaccharide and polyphenol may affect their physicochemical properties and functional activity respective, which also alter the nutritional and sensory qualities of food. This paper describes the means of characterizing food-derived polysaccharide and polyphenol interactions, including Fourier transform infrared (FT-IR) spectroscopy and nuclear magnetic resonance (NMR) spectroscopy, and interaction mechanisms such as enzyme-catalyzed reactions and free radical-induced reactions was also summarized. In addition, this paper focuses on the effects of concentration, pH, temperature and ionic strength on the interaction between polysaccharides and polyphenols, and further generalizes the alteration of physicochemical properties such as solubility and crystallinity, as well as bioactivities such as antioxidant and antimicrobial activities of polysaccharides and polyphenols under the interaction. Numerous research indicated that the formation of polysaccharide-polyphenol complexes had excellent biological activity and stability, promising good application prospects in food industry, healthcare, and other fields.